2020
DOI: 10.1002/nop2.438
|View full text |Cite
|
Sign up to set email alerts
|

Caring from the heart as belonging—The basis for mediating compassion

Abstract: Aim The aim of this study was to illuminate nurses’ experiences of mediating compassion to patients in the home care context. Design A phenomenological–hermeneutical approach was used. Methods The data comprised of texts from interviews with 12 nurses in a home care context. Informed consent was sought from participants regarding participation in the study and the storage and handling of data for research purposes. Results Four themes were seen: Encountering one another as human beings, Being in the moment, Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 51 publications
0
33
0
1
Order By: Relevance
“…55 Compassion is a merciful act 2 and is also seen as a personality trait which implies that it is a virtue, in other words, more than correctness or good behavior. 55 Compassion mediated by nurses can, according to [Hemberg and Wiklund Gustin, 2020], 56 be seen as a belonging between the nurse and the patient in a form of natural human-to-human-connection, and this is the element that unites and holds the caring relationship together. Compassion is demanding as it requires strength to face one's own emotions that arise from encountering suffering.…”
Section: Introductionmentioning
confidence: 99%
“…55 Compassion is a merciful act 2 and is also seen as a personality trait which implies that it is a virtue, in other words, more than correctness or good behavior. 55 Compassion mediated by nurses can, according to [Hemberg and Wiklund Gustin, 2020], 56 be seen as a belonging between the nurse and the patient in a form of natural human-to-human-connection, and this is the element that unites and holds the caring relationship together. Compassion is demanding as it requires strength to face one's own emotions that arise from encountering suffering.…”
Section: Introductionmentioning
confidence: 99%
“…53 In another study in Canada, the healthcare providers acknowledged that the occupational stressors inhibited their capacity to be compassionate. 62 Meanwhile, Hemberg and Gustin 14 argue that nurses should not focus only on practical and technical nursing skills and a greater focus should be placed on competencies such as compassion.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, Tehranineshat et al 63 found that building trust and using communication skills are instrumental for compassionate care delivery. In a qualitative study on 12 nurses in a home care context, Hemberg and Gustin 14 found that encountering patients as human beings can help to generate fundamental trust between nurses and patients, where the patient perceives the nurse as a reliable and honest person.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations